Gender-specific cut-off levels in colorectal cancer screening with fecal immunochemical test: A population-based study of colonoscopy findings and costs. (December 2021) - Ribbing Wilén, Hanna; Saraste, Deborah; Blom, Johannes
Objective: In the population-based Swedish regional colorectal cancer (CRC) screening program of Stockholm–Gotland using the fecal immunochemical test (FIT), gender-specific cut-off levels of fecal hemoglobin are applied, since previous studies have indicated a lower sensitivity of FIT for CRC in women. The aim was to evaluate the diagnostic yield and the screening costs overall and per detected CRC of this strategy. Methods: All individuals aged 60–69 invited to screening in 2015–2017 were included. Cut-off level for positive FIT was 40 µg/g in women and 80 µg/g in men. Those with a positive FIT were referred to colonoscopy. The yield of CRC and screening cost for the study period were assessed and compared to cut-off levels of 80 µg/g in both genders. Results: Approximately 230, 000 individuals were invited. Overall participation rates were 72% in women and 65% in men ( p  < 0.05). FIT was positive in 4256 individuals (2.7% in both genders). In 3758 colonoscopies, 258 (6.9%) CRCs were detected. The positive predictive value for CRC was significantly higher in men (8.3% vs. 5.8%). In 120 women with CRC, 28 (23%) had FIT < 80 µg/g. Negative colonoscopies were more common in women (24% vs. 17%, p < 0.05). Total costs for the study period were 52, 000, 000SEK (≈5, 200, 000€), i.e. 16% higher compared to using cut-off levels of 80 µg/g in both genders, and corresponding to a 3% increment in cost per detected CRC. Conclusion: The high rate of CRC detected in women in the lowest FIT category outweighs the minor reduction in screening costs if the same cut-off level was used as for men.